Environmental History of African Populations in the Três Picos State Park in the State of Rio de Janeiro - Wallace Marcelino da Silva; Carlos José Saldanha Machado; Rodrigo Machado Vilani (Ambiente & Sociedade)
Abstract During the colonial era in the Americas, Brazil received the largest contingent of enslaved Africans. These individuals’ encountered landscapes distinct from their countries of origin, interacted with them, and transformed them. This study aims to describe and analyse the African influence on the Três Picos State Park, located in the state of Rio de Janeiro. The methodological approach involved qualitative research, focusing on Environmental History through bibliographic and documentary analysis. Black Environmental History studies remain scarce in Brazil, and this article may serve as a contribution to further research in protected areas of the Atlantic Forest. The study concludes that a significant part of the park’s ecological reality bears a Black cultural heritage.